Quo Vadis of Sustainable Development of The Energy Sector in Indonesia - Ali, Chaidir -; Irvansyah, Dedek - (Sekolah Tinggi Manajemen IPMI, 2024)
Sustainable development in the energy sector is a necessity, because the need for energy remains constant if not increasing due to population growth. This phenomenon also applies to Indonesia, which unfortunately has not yet properly implemented the concept of sustainable development in the energy sector. This research finds the urgency is because Indonesia does not yet have a clear direction in sustainable development in the energy sector. Using normative research methods with an evaluative approach, this research discovered the fact that the direction of sustainable development in the energy sector in Indonesia does not yet have a legal basis that regulates it comprehensively. Apart from that, population planning factors and providing energy subsidies are an integral part that cannot be separated in order to achieve successful implementation of sustainable development in the energy sector.